A global analysis of the role of uncertainty, globalisation, security and market concentration on domestic capital formation - Gildas Dohba Dinga; Gisele Mah (Research in Globalization)
This paper studies the dynamics between domestic physical capital formation and selected macroeconomic indicators (uncertainty, globalisation, security and market concentration) that have been given little consideration both within the theoretical scope and empirical perspectives. Based on a panel of 93 countries and a time frame from 1995 to 2019, we employ the dynamic common correlation effect technique and the quantile-on-quantile approach to attain the objectives of the study. The outcome from the estimated models indicates that security expenditure and globalisation (especially economic globalisation, trade globalisation, social globalisation, interpersonal globalisation and cultural globalisation) augment domestic capital formation globally, but heterogeneity in results exist when the panel is subdivided into income levels and sub-regions, whereas market concentration and uncertainty indicate no significant effect on capital formation though negative with some heterogeneity observed at income levels, sub-regional groupings and different quantiles. We recommend a global consensus in the world at large to tackle the negative effect of uncertainty. The diversification of markets in less developed countries is equally vital to boost domestic capital formation. The enforcement of security within nations is equally vital to boost business confidence.